Prolonged therapeutic hypothermia does not adversely impact neuroplasticity after global ischemia in rats - Silasi, G.; Klahr, A.; Hackett, Mark; Auriat, A.; Nichol, H.; Colbourne, F. (2012)
Hypothermia improves clinical outcome after cardiac arrest in adults. Animal data show that a day or more of cooling optimally reduces edema and tissue injury after cerebral ischemia, especially after longer intervention delays. Lengthy treatments, however, may inhibit repair processes (e.g., synaptogenesis). Thus, we evaluated whether unilateral brain hypothermia (33°C) affects neuroplasticity in the rat 2-vessel occlusion model. In the first experiment, we cooled starting 1 hour after ischemia for 2, 4, or 7 days. Another group was cooled for 2 days starting 48 hours after ischemia. One group remained normothermic throughout. All hypothermia treatments started 1 hour after ischemia equally reduced hippocampal CA1 injury in the cooled hemisphere compared with the normothermic side and the normothermic group. Cooling only on days 3 and 4 was not beneficial. Importantly, no treatment influenced neurogenesis (Ki67/Doublecortin (DCX) staining), synapse formation (synaptophysin), or brain-derived neurotropic factor (BDNF) immunohistochemistry. A second experiment confirmed that BDNF levels (ELISA) were equivalent in normothermic and 7-day cooled rats. Last, we measured zinc (Zn), which is important in plasticity, with X-ray fluorescence imaging in normothermic and 7-day cooled rats. Hypothermia did not alter the postischemic distribution of Zn within the hippocampus. In summary, cooling significantly mitigates injury without compromising neuroplasticity. © 2012 ISCBFM All rights reserved.